2010
DOI: 10.1093/ndt/gfq274
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of nephropathy with apoA-1 mimetic peptide in apoE-deficient mice

Abstract: Background. There is mounting evidence that dyslipidaemia may contribute to development and progression of renal disease. For instance, hyperlipidaemia in apolipoprotein E-deficient (apoE −/−) mice is associated with glomerular inflammation, mesangial expansion and foam cell formation. ApoA-1 mimetic peptides are potent antioxidant and anti-inflammatory compounds which are highly effective in ameliorating atherosclerosis and inflammation in experimental animals. Given the central role of oxidative stress and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The current working model for the mechanism of action of apoA‐I mimetic peptides is their ability to bind15 and remove16 oxidized lipids and thereby to inhibit inflammatory responses. Previous studies have demonstrated that the overall oxidant status, especially in lipoproteins, is altered from being pro‐oxidative to one that is antioxidative after apoA‐I mimetic peptide treatment 19–22. Reactive oxygen species (ROS) are produced during cellular metabolism and also participate as important mediators of signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The current working model for the mechanism of action of apoA‐I mimetic peptides is their ability to bind15 and remove16 oxidized lipids and thereby to inhibit inflammatory responses. Previous studies have demonstrated that the overall oxidant status, especially in lipoproteins, is altered from being pro‐oxidative to one that is antioxidative after apoA‐I mimetic peptide treatment 19–22. Reactive oxygen species (ROS) are produced during cellular metabolism and also participate as important mediators of signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HDL and ApoAI are able to prevent adhesion of monocytes to endothelial cells, by reducing LDL-induced expression of adhesion molecules such as vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 on endothelial cells and CD 11b on monocytes (84,85). In fact, the significant anti-inflammatory properties of ApoAI have led to the potential use of ApoAI mimetic peptides as a therapeutic tool in treatment of a variety of inflammatory conditions (86,87). The health benefits of HDL antiinflammatory function go beyond its cardioprotective role as there is evidence that HDL can also play a role in prevention/reversal of chronic systemic inflammation by removing oxidized phospholipids and fatty acids from other lipoproteins and by eliminating proinflammatory molecules such as endotoxins and serum amyloid-A (SAA) (88-90).…”
mentioning
confidence: 99%
“…The ability of HDL to inhibit oxidative stress was supported in a recent study showing both mimetic peptides of apolipoprotein AI (ApoAI) and reconstituted discoidal HDLs (rHDLs) reduced NAD(P) H activation in an experimental model of nephropathy. 32 This broad spectrum of effects provides a functional basis for their therapeutic benefit in many complex, multigenic pathologies, such as atherosclerosis and rheumatological conditions. We investigate the effect of elevation of plasma HDL concentration as a therapeutic treatment for AAA.…”
mentioning
confidence: 99%